Studi Korelasi Karakteristik Dengan Perilaku Keluarga Dalam Upaya Penanggulangan Malaria Di Kecamatan Kintap Kabupaten Tanah Laut Propinsi Kalimantan Selatan Periode September-Desember Tahun 2007 - Nugroho, Adi; Ilmi, Bahrul; Marliani, Marliani (Jurnal Promosi Kesehatan Indonesia, 2008)
Background : Malaria is disease infection parasite caused by Plasmodium attacking eritrosite (red corpuscle) and marked with finding asexual form in blood that able to character of acute and cronic. The highest value malaria incidence happened in regency Tanah Laut Province of South Kalimantan there are in work region Puskesmas Kintap, in district Kintap.Therefore the aim of this study was to analized characteristic correlation study such as old, education, occupation, amount members of family and salary with behavior of family in the effort to handled malaria in district Kintap.Method : This study was designed as survey analytic with cross sectional design with simple random sampling technique, conducted in September-December 2007. Sample in this research is households with head of family, sample size was 99 households with head of family stayed in district Kintap. Analysis data the statistical test that is Chi-Square with interval confidence 95% with SPSS 12 for Windows program.Result : Statistical result for old characteristic (p=0,174), education (p=0,581), amount members of family ( p=0,639 (two tail) and p=0,336 (one tail), occupation (p=0,893) and salary (p=0,024). It is concluded that salary characteristic have a related to the behavior in the effort to handled malaria.Keywords : characteristic, malaria incidence, behavioral factor.